Just have a quick question whether my answer is correct. So consider the statement:
[\forall y \in Y: \exists x \in X: f(x)=y]\implies [\forall B_{1}\in P(Y): \forall B_{2} \in P(Y): \Phi(B_{1})=\Phi(B_{2}) \implies B_{1}=B_{2}]
We had to give the negation of this statement and I said the statement is of the form P \implies (Q \implies R) so the negation is P \wedge (Q \wedge \neg R) and then I got this as the negation:
[\forall y \in Y: \exists x \in X: f(x)=y]\wedge [\forall B_{1}\in P(Y): \forall B_{2} \in P(Y): \Phi(B_{1})=\Phi(B_{2}) \wedge B_{1}≠B_{2}]